Jupiter's Temperate Belt/Zone Contrasts Revealed at Depth by Juno Microwave Observations. Issue 10 (28th October 2021) - Fletcher, L. N.; Oyafuso, F. A.; Allison, M.; Ingersoll, A.; Li, L.; Kaspi, Y.; Galanti, E.; Wong, M. H.; Orton, G. S.; Duer, K.; Zhang, Z.; Li, C.; et al.
Abstract: Juno microwave radiometer (MWR) observations of Jupiter's midlatitudes reveal a strong correlation between brightness temperature contrasts and zonal winds, confirming that the banded structure extends throughout the troposphere. However, the microwave brightness gradient is observed to change sign with depth: the belts are microwave‐bright in the p < 5 bar range and microwave‐dark in the p > 10 bar range. The transition level (which we call the "jovicline") is evident in the MWR 11.5 cm channel, which samples the 5–14 bar range when using the limb‐darkening at all emission angles. The transition is located between 4 and 10 bars, and implies that belts change with depth from being N H 3 ‐depleted to N H 3 ‐enriched, or from physically warm to physically cool, or more likely a combination of both. The change in character occurs near the statically stable layer associated with water condensation. The implications of the transition are discussed in terms of ammonia redistribution via meridional circulation cells with opposing flows above and below the water condensation layer, and in terms of the "mushball" precipitation model, which predicts steeper vertical ammonia gradients in the belts versus the zones. We show via the moist thermal wind equation that both the temperature and ammonia interpretations can lead to vertical shear on the zonal winds, but the shear is ∼ 50 × weaker if only N H 3 gradients are considered. Conversely, if MWR observations are associated with kinetic temperature gradients then it would produce zonal winds that increase in strength down to the "jovicline", consistent with Galileo probe measurements; then decay slowly at higher pressures. Plain Language Summary: One of the core scientific questions for NASA's Juno mission was to explore how Jupiter's famous banded structure might change below the top‐most clouds. Did the alternating bands of temperatures, winds, composition, and clouds simply represent the top of a much deeper circulation pattern? Juno's microwave radiometer is capable of peering through the clouds to reveal structures extending to great depths, and has revealed a surprise: belts and zones do persist to pressures of 100 bars or more, but they flip their character at a level which we call the "jovicline, " coinciding with the depths at which water clouds are expected to form and generate a stable layer. This transition from microwave‐bright belts (ammonia depleted and/or physically warm) in the upper layers, to microwave‐dark belts (ammonia enriched or physically cool) in the deeper layers, and vice versa for the zones, may have implications for the shear on the Jupiter's zonal winds, indicating winds that strengthen with depth down to the jovicline, before decaying slowly at higher pressures. The origins of the transition is explored in terms of meridional circulations that change with depth, and in terms of models where strong precipitation dominates in the belts. Key Points: Banded structure of Jupiter's microwave brightness is correlated with the cloud‐top winds as far down as 100 bars Belt/zone contrasts flip sign in the 5–10 bar region, a transition layer coinciding with the water condensation level Transition can be explained by stacked meridional circulation cells and/or latitudinal gradients in precipitation